OP32 Health Inequalities in Japan 1986 to 2007 Based on Self-Rated Health, Household Income and a Novel Occupational Classification. (17th September 2012) - Hiyoshi, A; Shipley, MJ; Fukuda, Y; Brunner, EJ
Abstract : Background: While widening or stable inequalities have often been found in relation to economic stagnation in the west, time trends in health inequalities in Japan over the past two decades of economic stagnation are unclear. Comprehensive examination of temporal trends and factors contributing health inequalities in Japan are imperative to population health. Methods: We analysed a series of eight nationally-representative samples (Comprehensive Survey of the Living Conditions of People on Health and Welfare) between 1986 and 2007 (n=398, 303). We used household income and a novel theory-driven occupational social class classification to calculate temporal trends in relative and slope indices of inequality [RII and SII, respectively] in self-rated fair or poor health. Multiple imputation was conducted to account for missing income data. Effects of living conditions, behavioural and psychosocial factors were tested using 1998 and 2001 samples. Results: Overall, age-standardised self-rated fair or poor health showed U-shaped time trends in both sexes (quadratic term: men p<0.001, women p=0.005), with the lowest prevalence in early/mid 1990s. In men, income RII and SII narrowed significantly over the period (RII declined 1.4% per year, p=0.001; SII declined 0.1% per year, p=0.031). Inequalities in women's income were stable (RII and SII). The two indices showed constant inequalities across occupational social class in both sexes. After multiple imputation, point estimates became smaller, and narrowing of income inequality over time was significant for RII and SII in both sexes (p<0.05, n=490, 632). The annual declines were 1.4% and 1.0% for RII in men and women, respectively, and 0.1% for SII in both sexes. Living conditions, behavioural and psychosocial factors accounted for 28% of men's and 51% of women's health inequalities in Japan. Conclusion: Health inequalities in Japan either narrowed or remained stable from 1986 to 2007, in contrast to studies in western countries. The evidence provided by these analyses suggests that the prolonged economic stagnation in Japan had adverse effects at both ends of socioeconomic hierarchy. Potential explanations include effects of decreased income and increased stress in relation to job insecurity and workload across socioeconomic groups.